DETERMINAN KETIMPANGAN DISTRIBUSI PENDAPATAN DI KABUPATEN SUMBAWA - Nurma, Endang; Syafruddin, S (Jurnal Ekonomi & Bisnis, 2025)
This study aims to determine the effect of number of population, minimum wages, and economic growth on income distribution inequality in Sumbawa District in 2019-2023. The type of this study was associative study which aims to determine the direction and strength of the effect of the independent variables, namely number of population (X1), minimum wage (X2), and economic growth (X3) on the dependent variable, namely income distribution inequality in Sumbawa District in 2019-2023 (Y). The type of data used in this study was quantitative data obtained from secondary sources using documentation techniques. The data was processed using the SPSS application to be analyzed using multiple linear regression analysis techniques, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test) and coefficient of determination testing (R2). The results of this study showed that the number of population (X1), minimum wage (X2), and economic growth (X3) do not have a significant effect on income distribution inequality in Sumbawa District in 2019-2023, either partially or simultaneously. The percentage of the effect of population, minimum wages and economic growth on income distribution inequality in Sumbawa District was 2%, while the remaining of 98% was effected by other variables outside this study, such as unemployment, poverty, human development index.